2020
DOI: 10.1007/s00415-020-10285-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of patients infected with the SARS-CoV-2: a systematic review of the literature

Abstract: Objective To perform an updated review of the literature on the neurological manifestations of COVID-19-infected patients Methods A PRISMA-guideline-based systematic review was conducted on PubMed, EMBASE, and SCOPUS. Series reporting neurological manifestations of COVID-19 patients were studied. Results 39 studies and 68,361 laboratory-confirmed COVID-19 patients were included. Up to 21.3% of COVID-19 patients presented neurological symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 76 publications
3
60
1
7
Order By: Relevance
“…There was a lack of data regarding the association between hemorrhagic and ischemic stroke and the severity of the disease and mortality rate of patients with COVID-19. One study reported that 63% of COVID-19 patients who experienced ischemic stroke required admission to the intensive care unit (ICU) 50 .…”
Section: Resultsmentioning
confidence: 99%
“…There was a lack of data regarding the association between hemorrhagic and ischemic stroke and the severity of the disease and mortality rate of patients with COVID-19. One study reported that 63% of COVID-19 patients who experienced ischemic stroke required admission to the intensive care unit (ICU) 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Although COVID-19 is primarily a respiratory disease, neurological manifestations such as encephalopathy, acute cerebrovascular disease, epilepsy, and GBS are recognized as potential complications [ 2 4 ]. As COVID-19 continues to spread worldwide, relatively rare neurological phenomena associated with SARS-CoV-2 infection are increasingly reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients typically present with fever, cough, shortness of breath, myalgia, and fatigue, neurological manifestations involving the central and peripheral nervous system have been reported since the beginning of the pandemic [ 2 ]. Commonly described neurological manifestations include impairment of smell and taste, encephalopathy, acute cerebrovascular disease, epilepsy, and Guillain–Barré syndrome (GBS) [ 2 4 ]. In context of the large volume of COVID-19 cases, relatively rare post-infectious or para-infectious descriptions of movement disorders, predominately involving acute-onset myoclonus or cerebellar ataxia, are becoming increasingly evident.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, data are emerging on the neuropsychiatric complications associated with COVID-19 infections, which have shown similar prevalences ( 12 , 13 ). There have been some data to suggest that COVID-19 is associated with new-onset psychiatric disorders such as psychosis ( 14 , 15 ), however at the time of writing there is insufficient evidence to confirm this association ( 10 , 16 ).…”
Section: Introductionmentioning
confidence: 99%